2018
DOI: 10.1002/ijc.31938
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for preterm delivery among early onset cancer survivors: A Finnish register‐based study

Abstract: Previous studies have shown an elevated risk for preterm delivery among early onset cancer survivors. Whether the preterm delivery starts spontaneously, due to possible uterine damage because of cancer treatment, or is induced due to maternal conditions is unclear. Our aim was to assess pregnancy related conditions in female cancer survivors possibly underlying the elevated risk for preterm labor. Nationwide cancer and birth registries were merged to identify 1,753 first deliveries of cancer survivors (diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(57 reference statements)
0
2
0
Order By: Relevance
“… 45 , 46 Higher risks for pregnancy complications, including gestational diabetes mellitus, hypertension, and preeclampsia, have also been reported in women achieving a pregnancy after ART as well as in pregnant survivors of early-onset cancer. 47 , 48 , 49 , 50 , 51 Thus, pregnancy complications might also contribute to the increased risk of preterm births or lower birth weight observed in our study.…”
Section: Discussionmentioning
confidence: 64%
“… 45 , 46 Higher risks for pregnancy complications, including gestational diabetes mellitus, hypertension, and preeclampsia, have also been reported in women achieving a pregnancy after ART as well as in pregnant survivors of early-onset cancer. 47 , 48 , 49 , 50 , 51 Thus, pregnancy complications might also contribute to the increased risk of preterm births or lower birth weight observed in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, a Scottish study among 917 women with a previous history of cancer showed no elevated levels of preeclampsia (aOR 1.07, 95% CI 0.78 to 1.48) . This was also the case in a Finnish study among 1753 female cancer survivors (diagnosed below 40 years of age) where the overall risk for preeclampsia was not increased (aOR 1.11, 95% CI 0.85 to 1.45) . There are several risk factors for developing preeclampsia and being overweight or obese is the most important factor .…”
Section: Discussionmentioning
confidence: 90%